Literature review of spontaneous subarachnoid haemorrhage: treatment management and prevention (Part II) - J. Grigaitė; G. Rutkauskaitė; L. Piliponis; J. Ščerbak; D. Jatužis; J. Valaikienė (Neurologijos seminarai)
The most effective treatments for intracranial aneurysms are surgical clipping and endovascular coiling. Endovascular treatment has a lower risk of early death and complications, especially in the case of posterior circulation aneurysms, whereas the risk of recanalization and rupture of the aneurysm remains high therefore long-term follow-up is needed. Meanwhile, the long-term benefits of clipping are very important for younger patients, and in some cases it is a first-line treatment option. Interventional treatment of aneurysms is recommended as early as feasible. To avoid complications, all patients with spontaneous subarachnoid hemorrhage are recommended to undergo transcranial dopplerography daily or every other day, as well as head computed tomography, computed tomography angiography (CTA), computed tomography perfusion or digital subtraction angiography on the day of hospitalization, 3-5 and 7-10 days. For the prevention of late cerebral ischemia, it is recommended to administer calcium channel blocker nimodipine and to maintain euvolemia. If cerebral vasospasm occurs, euvolemic-induced hypertension and, in some cases, endovascular treatment such as intra-arterial vasodilator therapy or/and angioplasty are recommended. The choice of treatment tactics for unruptured intracranial aneurysms depends on the natural course of the disease and the risk of rupture, which can be assessed using various scales. Following monitoring tactics, it is recommended to repeat CTA or magnetic resonance angiography (MRA) in 6 to 12 months after the aneurysm is detected to evaluate changes over time. CTA and MRA are also recommended for people with two or more family members with unruptured intracranial aneurysms or the diagnosis of SAH and other risk factors. Patients who are accidentally diagnosed with an unruptured aneurysm are recommended to quit smoking, have their blood pressure measured periodically, and avoid heavy weights.